DALES, Drug Allergy Labels in Elective Surgical patients: a prospective, multicentre cross-sectional study of prevalence, nature and anaesthetists' approach to management. (December 2021) - Thomas, Caroline; Clark, Sam; Fallaha, David; Wilson, Michelle; Hopkins, Philip M.; Savic, Sinisa; Savic, Louise; ,
Abstract: Background: We sought to define the prevalence and nature of patient-reported drug allergies, determine their impact on prescribing, and explore drug allergy knowledge and attitudes amongst anaesthetists. Methods: We performed a prospective cross-sectional study in 213 UK hospitals in 2018. Elective surgical patients were interviewed, with a detailed allergy history taken in those self-reporting drug allergy. Anaesthetists completed a questionnaire concerning perioperative drug allergy. Results: Of 21 219 patients included, 6214 (29.3 %) (95% confidence interval [CI]: 28.7–29.9) reported drug allergy. Antibiotics, NSAIDs, and opioids were the most frequently implicated agents. Of a total of 8755 reactions, 2462 (28.1%) (95% CI: 29.2–31.1) were categorised as high risk for representing genuine allergy after risk stratification. A history suggestive of chronic spontaneous urticaria significantly increased the risk of reporting drug allergy (odds ratio 2.68; 95% CI: 2.4–3; P <0.01). Of 4756 anaesthetists completing the questionnaire, 1473 (31%) (95% CI: 29.7–32.3) routinely discuss perioperative allergy risk with patients. Prescribing habits in the presence of drug allergy labels differ depending on the implicated agent. Most anaesthetists (4678/4697; 99.6%) (95% CI: 99.4–99.8) prescribe opioids when reactions are consistent with side-effects, although 2269/4697 (48%) (95% CI: 46.9–49.7) would avoid the specific opioid reported. Conclusions: Almost 30% of UK elective surgical patients report a history of drug allergies, but the majority of reported reactions are likely to be non-allergic reactions. Allergy labels can impact on perioperative prescribing through avoidance of important drugs and use of less effective alternatives. We highlight important knowledge gaps about drug allergy amongst anaesthetists, and the need for improved education around allergy.